2020
DOI: 10.1080/22221751.2020.1713706
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lethal HPAIV H5N8 clade 2.3.4.4B infection in AIV pre-exposed mallards

Abstract: In 2016/2017, a severe epidemic of HPAIV H5N8 clade 2.3.4.4 group B (H5N8B) affected Europe. To analyse the role of mallards in the spatiotemporal dynamics of global HPAIV H5N8B dispersal, mallards (Anas platyrhynchos), naturally exposed to various AIV and therefore seropositive, were challenged with H5N8B. All experiments were controlled by infection and co-housing of seronegative juvenile Pekin ducklings. All ducks that survived the first infection were rechallenged 21 dpi with the homologous H5N8B strain. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 45 publications
5
34
0
Order By: Relevance
“…Evidence for the presence of HPAI H5-specific antibodies in various species of wild ducks was obtained during surveillance studies in Asia and Europe [ 20–22 ]. Moreover, an experimental infection study with Pekin ducks and mallards showed that ducks surviving infection with a H5N8 group B virus were protected from re-infection with the homologous virus [ 38 ]. The pre-existing immunity in the wild bird population thus may have further hampered the spread of genetically related H5N6 group B virus during the 2017–2018 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the presence of HPAI H5-specific antibodies in various species of wild ducks was obtained during surveillance studies in Asia and Europe [ 20–22 ]. Moreover, an experimental infection study with Pekin ducks and mallards showed that ducks surviving infection with a H5N8 group B virus were protected from re-infection with the homologous virus [ 38 ]. The pre-existing immunity in the wild bird population thus may have further hampered the spread of genetically related H5N6 group B virus during the 2017–2018 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HPAI H5 virus and/or HPAI H5-specific antibodies in live birds suggests that (some individuals of) these bird species can (asymptomatically) carry the virus and act as a vector. Experimental infections in captivity confirmed differences among bird species’ susceptibility to infection and/or disease [ 132 , 133 , 135 , 139 , 140 , 141 , 142 , 143 ]. Given the heterogeneity among individuals in susceptibility to infection and disease, in some cases a single species can act as vector as well as a sentinel [ 132 , 133 , 135 , 139 ].…”
Section: Underlying Mechanisms Of Emergence Of Novel Hpai H5 Virusmentioning
confidence: 93%
“…Susceptibility to infection and disease has also been shown to differ among HPAI H5 virus lineages. For instance, Pekin ducks showed variable susceptibility to disease; exposure to HPAI clade 2.3.4.4a H5N8 2014 resulted in 60% mortality [ 134 ], while exposure to HPAI clade 2.3.4.4b H5N8 2016 or H5N6 2017 resulted in 100% mortality [ 134 , 135 ]. Based on field surveillance data, more wild birds died during the circulation of clade 2.3.4.4b H5N8 2016 than during the circulation of clade 2.3.4.4b H5N6 2017 [ 134 ].…”
Section: Underlying Mechanisms Of Emergence Of Novel Hpai H5 Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are supported by a number of studies from different parts of the world such as in Iran in 2015 [ 33 ] and two zoos in Delhi and Madhya Pradesh in 2016 [ 34 ]. Moreover, some birds which are naturally pre-exposed to LPAIV can play a role as AIV reservoir and play a role in virus transmission to susceptible host species and sometimes have homologous immunity that prevent the transmission [ 35 ].…”
Section: Discussionmentioning
confidence: 99%